Pengaruh Konsentrasi Beauveria Bassiana Terhadap Intensitas Serangan Serangga Hama Ulat Daun (Plutella xylostella L.), Pertumbuhan Dan Hasil Beberapa Varietas Pakcoy (Brassica rapa L.) - Muhammad Rahmadani Darusman; Ai Komariah; Elly Roosma Ria (Paspalum: Jurnal Ilmiah Pertanian, 2024)
This research aims to determine the interaction between administering concentrations of B. bassiana and several varieties on attacks by leaf caterpillar insect pests in increasing plant growth, plant fresh weight and quality of pakcoy plants. The experiment was carried out on experimental land in Cibedug Village, Cikole Village, Lembang District, West Bandung Regency with an altitude of 1100 m above sea level (asl) with Andisol soil order and was carried out from August 2023 to September 2023. The experimental design used was an environmental design experiment using a Split Plot Design consisting of 12 treatment combinations repeated 3 times. consists of two treatment factors, namely B. bassiana concentration (K) with the following levels: k0 : 0 g L-1 Solution (control), k1 : 2 g L-1 Solution, k2 : 4 g L-1 Solution and k3 : 6 g L-1 Solution and the second factor are several Pakcoy varieties (V) with the following levels: v1: Nauli F1 variety, v2: Flaminggo variety, v3: Masbro variety, which is repeated three times. The results of the research showed that there was no interaction between the concentration of B. bassiana and several pak choy varieties on all observed parameters. Giving a B.bassiana concentration of 4 g L-1 Solution had the most efficient effect on the intensity of attacks, weight and length of the 3rd instar larvae of P.xylostella. The Nauli F1 variety gave the best results in terms of plant height and number of leaves and the Flaminggo variety gave the best results in terms of fresh weight per plant and fresh weight per plot.